2006
DOI: 10.1271/bbb.50694
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of Amylolytic Genes inAspergillus nidulans

Abstract: Aspergillus nidulans possessed 16 putative amylolytic genes consisting of 7 alpha-glucosidase (agdA-F), 7 alpha-amylase (amyA-F), and 2 glucoamylase (glaA and B) genes on the genome. Among them, the agdA, agdB, agdE, agdF, amyA, amyB, amyF, and glaB genes were induced by isomaltose. AmyR, a Zn(II)(2)Cys(6) transcription factor, was required for the induction. The isomaltose-inducible genes possessed at least one consensus sequence for AmyR binding, 5'-CGGN(8)CGG, on each promoter region. None of the amylolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…This study describes that neither a knockout of agtA nor overexpression of AgtA or AgtB had an effect on the ability of A. niger strains to grow on starch, even if the parental strain was severely hampered in this trait. In another study, we have also shown that expression of the agtA and agtB genes is not regulated by AmyR, the general regulator for starch-processing enzymes in aspergilli (X.-L. Yuan et al, unpublished data) (56), and similar results were found for the homologous genes in Aspergillus nidulans (51). Taken together, these data indicate that the Agt proteins most likely are not involved in starch catabolism.…”
Section: Discussionsupporting
confidence: 70%
“…This study describes that neither a knockout of agtA nor overexpression of AgtA or AgtB had an effect on the ability of A. niger strains to grow on starch, even if the parental strain was severely hampered in this trait. In another study, we have also shown that expression of the agtA and agtB genes is not regulated by AmyR, the general regulator for starch-processing enzymes in aspergilli (X.-L. Yuan et al, unpublished data) (56), and similar results were found for the homologous genes in Aspergillus nidulans (51). Taken together, these data indicate that the Agt proteins most likely are not involved in starch catabolism.…”
Section: Discussionsupporting
confidence: 70%
“…From two partially randomized libraries, Kojima et al obtained CGG triplets that were considered critical for effective AmyR-DNA interaction, and one other sequence that was found in the upstream region of AmyR-regulated gene amyB. 14) In addition, the authors also suggested the 8-base intermediate region between the two CGG triplets was not composed of random bases, but preferred thymine at certain positions. 13) In order to prove that the bead display system is adequate for full-scale, high-throughput TFBS characterization, we applied a strategy different from the previous trial.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the motif derived from group I, desinated CGGNNNTTTNTCGG, with the upstream regions (1,000 bases) of eight A. nidulans AmyR-related genes (agdA, agdB, agdE, agdF, amyA, amyB, amyF, and glaB) that are induced by isomaltose in an AmyRdependent manner, 14) as well as two corresponding regions of agdD and amyD. Although consensus AmyRbinding sequence CGGN 8 CGG was found in every promoter of these 10 genes, we noticed that only a fraction of them clearly showed AmyR-dependent induction.…”
Section: Binding Site Analysis Of Amyr-related Gene Promoters Of a Nmentioning
confidence: 99%
“…[25][26][27] AmyR binds to the direct repeat of CGG triplets separated by 8 bases in the various amylase promoter regions or the CGGN 8 AGG site of the Taka-amylase A promoter. 25,[28][29][30] In this study, subcellular localization studies and C-terminal truncation analysis of AmyR were carried out to obtain insight into the mechanisms of AmyR mediated induction. We found that nuclear accumulation of the GFP-AmyR fusion protein is triggered by the -amylase inducer isomaltose.…”
mentioning
confidence: 99%